Learning from the minds of others: A review of social cognition treatments and their relevance to traumatic brain injury. Issue 1 (2nd January 2019) - Cassel, Anneli; McDonald, Skye; Kelly, Michelle; Togher, Leanne
ABSTRACT: Social cognition is widely regarded as an essential skill with which to understand the social world. Despite this, the role that social cognition plays in outcome, and whether deficits are remediable after traumatic brain injury (TBI), are not yet well known. The current review examines the construct of social cognition and presents a conceptual biopsychosocial model with which to understand the social cognitive process. This is related to the literature on social cognitive deficits in TBI and we discuss relevant treatment developments to date within this population. We then review social cognition treatment programmes researched in other clinical populations in order to advise and inform approaches for those living with TBI. Whilst treatments have focused on emotion perception skills in the TBI literature, programmes developed for other clinical populations have had broader targets, focusing on Theory of Mind skills and/or modifying interpretational cognitive biases. Moreover, they have largely proven to be efficacious. Programmes that are contextualised, collaborative, and experiential seem optimal in enabling generalisation relevant to individuals' everyday social lives. We argue that there is therefore scope to improve the evidence-based social cognitive treatment options available for those with TBI, taking into account specific adaptations necessary for this population.